2021
DOI: 10.1007/s11618-021-01006-7
|View full text |Cite
|
Sign up to set email alerts
|

Fernbeschulung während der COVID-19 bedingten Schulschließungen weiterführender Schulen: Analysen zum Gelingen aus Sicht von Schülerinnen und Schülern

Abstract: ZusammenfassungIm Zuge der Schulschließungen im Rahmen der Schutzmaßnahmen gegen COVID-19 standen deutsche Schulen historisch erstmals vor der Aufgabe, flächendeckende Fernbeschulung für Schülerinnen und Schüler zu gewährleisten. Der über Nacht einsetzenden Herausforderung zur Konzeptionierung und Durchführung dieses Unterrichts auf Distanz begegneten Schulen, Lehrkräfte und Lernende in vielfacher Weise, ohne auf bewährte Strukturen zurückgreifen zu können. Der Beitrag entwirft anhand des Angebots-Nutzungs-Mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
29
1
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(37 citation statements)
references
References 15 publications
4
29
1
3
Order By: Relevance
“…In early COVID-19 pandemic-related educational research, many scholars attempted to answer these questions from a theoretical (e.g., Klieme, 2020;Köller et al, 2020;Meyer, 2020;Voss and Wittwer, 2020), quantitative (e.g., Grewenig et al, 2020;Huber and Helm, 2020a;Porsch and Porsch, 2020;Holzer et al, 2021;Steinmayr et al, 2021) and qualitative perspective (e.g., Frohn, 2020;. In line with some of these early research initiatives (e.g., Wildemann and Hosenfeld, 2020;Züchner and Jäkel, 2021) we adopted the CIPO/offer-and-use logic outlined above to delineate and identify relevant predictors of student learning during the pandemic. More specifically, we used models from homework research (e.g., Trautwein et al, 2006;Kohler, 2011).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 2 more Smart Citations
“…In early COVID-19 pandemic-related educational research, many scholars attempted to answer these questions from a theoretical (e.g., Klieme, 2020;Köller et al, 2020;Meyer, 2020;Voss and Wittwer, 2020), quantitative (e.g., Grewenig et al, 2020;Huber and Helm, 2020a;Porsch and Porsch, 2020;Holzer et al, 2021;Steinmayr et al, 2021) and qualitative perspective (e.g., Frohn, 2020;. In line with some of these early research initiatives (e.g., Wildemann and Hosenfeld, 2020;Züchner and Jäkel, 2021) we adopted the CIPO/offer-and-use logic outlined above to delineate and identify relevant predictors of student learning during the pandemic. More specifically, we used models from homework research (e.g., Trautwein et al, 2006;Kohler, 2011).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…For example, Champeaux et al (2020), Grewenig et al (2020), Zaccoletti et al (2020), Blume et al (2021), Nusser et al (2021), andSteinmayr et al (2021) used ratings from parents to predict the learning outcomes of children during the lockdown. Dietrich et al (2020), Huber and Helm C. (2020b), Grätz and Lipps (2021), Holzer et al (2021), Pelikan et al (2021) and Züchner and Jäkel (2021) used student data to explain selfreported ability to complete tasks during distance education. These studies identified several variables that significantly predicted the rated student outcomes of primary and/or secondary students during lockdown.…”
Section: Literature Review On Explanatory Studies Predicting Student ...mentioning
confidence: 99%
See 1 more Smart Citation
“…On part of the school students, the simple loss of effective learning time and the resulting learning lags seem most important [15]. Furthermore, factors such as a possible lack of support from parents and friends, a deprived social background, limited opportunities to ask understanding-related questions that are answered immediately, and a lack of familiarity with digital and self-regulated learning are discussed [59,61,64,65].…”
Section: Digital Teaching and Learning Before And During The Covid-19 Pandemicmentioning
confidence: 99%
“…Besides the financial burdens families face, parents need to engage with educational media matters: To receive learning material or contact their teacher, students in primary and secondary school need technical equipment. As children and adolescents might not be familiar with handling technical equipment, parents supported particularly young children's media use (Gerhardts et al, 2020;Züchner and Jäkel, 2021). Most students reported that necessary equipment was available (Wildemann and Hosenfeld, 2020), while between 3 and 25% had difficulties with the availability of technical equipment at home (Helm et al, 2021).…”
Section: Family Contextmentioning
confidence: 99%